EDUCATIONAL STORYTELLING IMPLEMNETATION TO IMPROVE KNOWLEDGE OF PACKAGED SWEETNED BEVERAGE DANGERS FOR EARLY CHILDHOOD KIDNEY HEALTH - Izzati, Aisyah; Tri, Nita (Jurusan Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2025)
The rising consumption of packaged sweetened beverages among children poses serious public health concerns, particularly for kidney health. These drinks, commonly containing high sugar levels, artificial colorings, and preservatives, are aggressively marketed to children through appealing packaging and strategic advertisement placements. Indonesia ranks third in Southeast Asia for sweetened beverage consumption, with 62% of children reportedly consuming them at least once a week. Despite the health risks, public awareness—especially among parents and educators—remains limited. This community service initiative aimed to educate kindergarten-aged children on the dangers of sugary packaged beverages through an interactive storytelling method at TK Aisyiyah 7, Magelang CityA total of 30 students participated in the activity, which involved pre- and post-assessment test using an interactive game-based questionnaire consisting of three short, image-supported questions related to the educational material to assess students’ knowledge before and after the intervention. An original storytelling session titled “The Adventure of the Brain, Kidney, and Bladder”, the use of educational puppets and visuals, and a health-themed sing-along. Results showed high engagement from children and improved knowledge retention as evidenced by increased post-test scores. The initiative successfully demonstrated that storytelling is an effective medium for early health education, fostering awareness of kidney health and promoting healthier beverage choices among young children.